Discovery of exolytic heparinases and their catalytic mechanism and potential application - Qingdong Zhang (Nature Portfolio, 2021)
Exolytic heparinases are needed for sequencing of heparin and heparan sulfate (HP), but have not yet been reported. Here, the authors identify exolytic heparinases from different bacteria and show that the heparinases preferentially digest HP, determine the crystal structure of the exoheparinase BlexoHep and perform sequencing of HP octasaccharides using the enzyme.